192. Predictors of Actionable Results on Gastrointestinal Panel Testing for Children Hospitalized with Acute Diarrheal Illnesses. (15th December 2022) - Ho, Erin; Dominguez, Samuel R; Cotter, Jillian; Thomas, Jacob
Abstract: Background: Among hospitalized children with acute diarrheal illnesses, multiplex PCR gastrointestinal panels (GIP) are commonly overused. GIPs are most likely to impact management and outcomes if an actionable (bacterial or parasitic) result is obtained. To inform future diagnostic stewardship, we evaluated which clinical factors, including provider-reported test indications and stool frequency, were associated with actionable results. Methods: This is a multicenter cross-sectional study of children ≤ 18 years old hospitalized at any Children's Hospital Colorado site between 2015-2018 with a diarrheal illness and at least one GIP performed. We used multivariable logistic regression to determine associations between actionable GIP results and testing indication, stool frequency, and demographics. We evaluated these findings in two subgroups - patients with at least one complex chronic condition (CCC) and non-CCC patients. Results: There were 1, 124 GIPs performed for 967 encounters. Yield of actionable results was higher for non-CCC than CCC patients (30% vs. 21%, p < .001) (Image 1), and test indications differed between the two groups (Table 1). For non-CCC patients, we found positive associations between actionable results and "Diarrhea with blood or pus" test indication (relative risk (RR) 1.5, confidence limits (CL) 1.09-2.07, p = .01), summer season (RR 1.69, CL 1.14-2.5, p =.01), and age ≥1 yr (RR 2.88, CL 1.82-4.54, p< .001). Male gender was negatively associated (RR 0.75, CL 0.58-0.96, p=.02). For CCC patients, age ≥1 yr was positively associated with actionable results (RR 3.17, CL 1.59-6.32, p = .001). ≥4 stools per day (RR 0.73, CL 0.54-.99, p=0.04) and ICU admission (RR 0.69, CL 0.5-0.95, p=0.2) were negatively associated with actionable results (Table 2). Conclusion: For both cohorts, age ≥1 was positively associated with actionable GIP results. For otherwise healthy children, bloody diarrhea and summertime were positively associated with actionable results. CCC patients had less frequent actionable results, and no GIP indications were predictive of actionable results. A higher stool burden did not statistically increase the probability of an actionable result in either cohort. These results may guide diagnostic stewardships efforts for GIP ordering in pediatric patients. Disclosures: Samuel R. Dominguez, MD PhD, Biofire DIagnostics: Advisor/Consultant|Biofire DIagnostics: Grant/Research Support|DiaSorin Molecular: Advisor/Consultant|Karius: Advisor/Consultant|Pfizer: Grant/Research Support.